Survival in a falling market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Country Director of Technoserve Tanzania, a non-government organisation, explains how the Tanzanian coffee market has been affected by a global glut in coffee production, and how both the government and the Tanzanian farmers need to improve their management of coffee production, so that it can compete with low-cost foreign coffee.